Penegakan Hukum Terhadap Pelanggaran Lalu Lintas Dan Modifikasi Kendaraan Bermotor Ilegal Di Kota Denpasar - I Dewa Gde Surya Wibawa; Putu Lantika Oka Permadhi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
Law No. 22 of 2009 concerning Traffic and Road Transportation in Article 106 paragraph (1) states that every person who drives a vehicle is obliged to obey traffic regulations and create road safety. But in reality, there are still traffic violations, especially illegal modifications to motor vehicles that endanger the safety and comfort of other drivers. Empirical legal research, or law as a social or cultural reality, is the methodology used. The conclusion of this study is that there are two methods used by law enforcement to combat traffic violations and unauthorized modifications to motor vehicles: indirect action, which involves giving warnings to violators. Law enforcement efforts and challenges, including repressive, preventive, and anticipatory measures. Factors of facility or infrastructure constraints and, factors of community constraints.